PENGARUH LINGKUNGAN KERJA NON FISIK, DISIPLIN KERJA DAN PENGAWASAN TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN LAPANGAN PADA PT. BUMI SAWIT PERKASA KAB. KAMPAR - Sri, Hartina; Marzolina, Marzolina; Ahmad, Rifqi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of non-physical work environment, work discipline and supervision on job satisfaction and employee performance. Locations in research at PT. Bumi Sawit Perkasa in the Kampar Regency area to be precise in Danau Lancang Village, Tapung Hulu District. The sample in this study amounted to 115 people using the saturated sample method. Because at the time of distributing the questionnaire, out of 115 respondents, 6 of them did not fill in, so only 109 respondents filled in and continued as research data. The data analysis technique used is path regression analysis. The results explained that non-physical work environment, work discipline and supervision had a significant effect on job satisfaction. Meanwhile, the path regression results explain the non-physical work environment, work discipline and supervision have a significant effect on employee performance through job satisfaction.Keywords: Non-Physical Work Environment, Work Discipline, Supervision, Job Satisfaction and Employee Performance